2007
DOI: 10.1002/cncr.23110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alpha‐actinin 4 and 67 kDa laminin receptor as stage‐specific markers in esophageal cancer via proteomic approaches

Abstract: Unlike other primary sensory neurons, the neurons in the mesencephalic trigeminal nucleus (Vmes) receive most of their synaptic input onto their somata. Detailed description of the synaptic boutons onto Vmes neurons is crucial for understanding the synaptic input onto these neurons and their role in the motor control of masticatory muscles. For this, we investigated the distribution of γ‐aminobutyric acid (GABA)‐, glycine‐, and glutamate‐immunopositive (+) boutons on Vmes neurons and their ultrastructural para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 34 publications
2
54
1
1
Order By: Relevance
“…At expression level different isoforms of TMP are regulated dissimilarly in tumors, implying that these isoforms may have different functions in cell transformation. TPM1 [23] and TPM2 [24] have shown to be subject of down-regulation while TPM4 [23] and TPM3 ( [25], and as our unpublished result indicates (in a study on cell lines)) are significantly subject of upregulation in ESCC tissues. In addition, fusion of TPM4-ALK was observed to happen in ESCC [24] which results in the up regulation of anaplastic leukemia kinase.…”
Section: Cytoskeletonsupporting
confidence: 53%
“…At expression level different isoforms of TMP are regulated dissimilarly in tumors, implying that these isoforms may have different functions in cell transformation. TPM1 [23] and TPM2 [24] have shown to be subject of down-regulation while TPM4 [23] and TPM3 ( [25], and as our unpublished result indicates (in a study on cell lines)) are significantly subject of upregulation in ESCC tissues. In addition, fusion of TPM4-ALK was observed to happen in ESCC [24] which results in the up regulation of anaplastic leukemia kinase.…”
Section: Cytoskeletonsupporting
confidence: 53%
“…Later, five groups reported proteomic signatures associated with ESCC using ESCC samples collected from different regions of China, including high risk areas for ESCC such as Linzhou, Xinjiang and low risk areas like Beijing and Guangdong, but only four reports displayed details of identified proteins. Interestingly, more overlap of the identified proteins came from Fu's study and ours, both of which used ESCC samples from Linzhou, one of the highest areas for ESCC adjacent to Taihang Mountain [Fu et al, 2007]. The commonly identified proteins with the same change direction included alpha enolase, TPM, tubulin, prohibitin and PRX2.…”
Section: Two-dimensional Electrophoresis-based Proteomic Findings Of mentioning
confidence: 78%
“…Our findings indicate that MIF may play crucial roles in malignant transformation of pathogenesis of EC and MIF could become a potential biomarker for high-risk population screening, assessment of therapeutic efficiency, prognostic evaluation, and molecular targets of developing novel therapeutic regimen as well. In addition of our proteomic results in ESCC, several other reports have looked at the clinical value of potential biomarkers, including cytokeratin 14, Annexin I, SCCA1/2, calgulanulin B and HSP 60, alpha-actinin 4 and 67 kDa laminin receptor, cathepsin D and PKM2, periplakin, calreticulin and GRP78, galectin-7, anti-CD25B antibody [Dong et al, 2010;Du et al, 2007;Fu et al, 2007;Hatakeyama et al, 2006;Liu et al, 2011;Nishimori et al, 2006;Zhu et al, 2010]. Nevertheless, further extensive studies are still necessary to determine the clinical utility of the identified proteins in tumorigenesis and progression of ESCC.…”
Section: Protein Name T/n Ratio Functions References Prohibitinmentioning
confidence: 89%
See 2 more Smart Citations